Evaluation of Streptococcus pneumoniae in bile samples: A case series review. Issue 6 (June 2016) - Itoh, Naoya; Kawamura, Ichiro; Tsukahara, Mika; Mori, Keita; Kurai, Hanako
Abstract: Although Streptococcus pneumoniae is an important pathogen of humans, pneumococcal cholangitis is rare because of the rapid autolysis of S. pneumoniae . The aim of this case series was to review patients with bile cultures positive for S. pneumoniae . This study was a single center retrospective case series review of patients with S. pneumoniae in their bile at a tertiary-care cancer center between September 2002 and August 2015. Subjects consisted of all patients in whom S. pneumoniae was isolated in their bile during the study period. Bile specimens for culture were obtained from biliary drainage procedures such as endoscopic retrograde biliary drainage, endoscopic nasobiliary drainage, and percutaneous transhepatic biliary drainage. There were 20 patients with bile cultures positive for S. pneumoniae during the study period. All patients presented with extrahepatic obstructive jaundice due to hepatopancreatobiliary tumors. Nineteen of 20 patients underwent the placement of plastic intrabiliary tubes. The mean time between the first-time drainage and the positive culture was 26 days (range 0–313 days). Although 12 of 20 patients met our definition of cholangitis, 5 were clinically treated with antibiotics based on a physician's assessment of whether there was a true infection. The present study is the largest case series of patients with S. pneumoniae in their bile. Based on our findings, the isolation of S. pneumoniae from bile may be attributed to the placement of biliary drainage devices.